Integrated supplier management system a case study : Parl Bone Mills [electronic resource] - 438358 Tanvi Rahman Bias; Othman Ibrahim (Skudai : Universiti Teknologi Malaysia, 2007)
Thesis (Sarjana Sains (Teknologi Maklumat - Pengurusan)) - Universiti Teknologi Malaysia, 2007